Propriedades vibracionais do Dipeptideo a-L-Aspartil-L-Alanina em condições extremas de temperatura - Pinheiro, Gardenia de Sousa (2013)
In the present study the dipeptide α-L-aspartyl-L-alanine (α-Asp-Ala) whose molecular formula is C7H12N2O5, was studied using vibrational spectroscopy (IR and Raman) and thermal analysis. The thermal analysis experiments (differential scanning calorimetry and thermogravimetric analysis) were performed in the temperature range 113-513 K. Raman spectroscopy experiments under extreme conditions of temperature (18-413 K) were performed in the spectral range 20-3400 cm-1. As complementary technique, spectroscopy experiments infrared in the temperature range 83-413 K in the spectral region between 400 and 4000 cm-1 were performed. From the analysis of the results, it is possible to conclude that: (i) no indication of a phase transition undergone by the α-Asp-Ala crystal at low temperatures (18 to 293 K) was observed, (ii) the studied material undergoes a reversible first order phase transition from order-disorder type at 373 K, where several changes were observed in the vibrational spectra, especially with vibrational modes of the units that participate directly of the hydrogen bonds; (iii) The phase transition undergone by the α-Asp-Ala crystal (about 373 K) involves changes in hydrogen bonds, possibly rupture of at least one of them, and change in the conformation of the molecules in the unit cell.